The crucial elements of classroom management - Rinda, Renata Kenanga; Indrastana, Nodistya Septian (Journal of English in Academic and Professional Communication, 2020)
The urgency of classroom management in the English classroom is indisputable. It is said so since classroom management is the fundamental component of the successful teaching and learning processes. However, many teachers are still confused about how to practice good classroom management. Coping with the previous dilemma, this paper aimed at describing the five crucial elements of practicing good classroom management. Those elements are listed as follows: teacher talk, teacher talking time, voice management, physical presence, and seating arrangement through a literature review. It is expected that this paper can give a clear explanation related to the five crucial elements. With that in mind, classroom management can be well-practiced.